Avaliação neuroquímica e comportamental em ratos submetidos ao modelo de depressão induzida por extinção - Almeida, Carla Biesdorf de (2015)
The absence of or loss of rewards or reinforces hold a major role in the development of depression in humans. Microdialysis studies in rats have generally shown that appetitive stimuli release dopamine (DA) in the nucleus accumbens (NAc). However, it is not clear how the extinction of a reward affect the DA release. Assessing the behavior and the release of DA in the NAc during delivery and extinction of reward (food) in rats submitted to the extinction-induced depression model. In vivo microdialysis was used to quantify the levels of DA in the NAc. Male Wistar rats were trained to receive food reward associated with appearance of cue-lights. The extinction happened when the cuelights were presented without the reward. Different protocols were used to assess the effects of extinction on the behavior and on the levels of DA and its metabolites. (a) during the period of cued reward delivery, DA levels increased significantly in the NAc core but not in the NAc shell; (b) the level of DA remained increased during extinction (the absence of reward with the cue lights presented) e non-extinction (absence of cue-lights); (c) when extinction was administered 1 hr after the reward, DA significantly decreased in the NAc core, but not in the NAc shell. The same happened when the extinction was administered 24 hrs after the last reward session; (d) grooming seems to be an extinction-induced behavior, and the glances toward the cue-lights an index of resistance to extinction. these results confirm the importance of dopamine release in the nucleus accumbens for reward-related states, with DA increasing in the core, but not shell subregion; b) provide evidence that during the withholding of expected reward, DA decreases in the NAc core, but not shell region; c) this decrease in DA appears only after a delay between delivery of reward and extinction likely due to it being masked by persisting post-reward DA release. We hypothesize the decrease in extinction-induced release of DA in the Nac core to be a marker for the despair/depression that is known to accompany the loss of expected rewards/reinforcers.